The neurobehavioral and molecular phenotype of Angelman Syndrome. (29th July 2015) - Wink, Logan K.; Fitzpatrick, Sarah; Shaffer, Rebecca; Melnyk, Sophia; Begtrup, Amber H.; Fox, Emma; Schaefer, Tori L.; Mathieu‐Frasier, Lauren; Ray, Balmiki; Lahiri, Debomoy; Horn, Paul A.; Erickson, Craig A.
<x xml:space="preserve">Abstract</x> Angelman Syndrome (AS) is a rare neurodevelopmental disorder associated with developmental delay, speech impairment, gait ataxia, and a unique behavioral profile. AS is caused by loss of maternal expression of the paternally imprinted UBE3A gene. In this study we aim to contribute to understanding of the neurobehavioral phenotype of AS with particular focus on the neuropsychiatric presentation of the disorder. We also undertake initial exploration of brain‐derived neurotrophic factor (BDNF) plasma levels in AS. Twelve individuals ages 3 years or older with a confirmed genetic diagnosis of AS underwent detailed medical history, phenotypic characterization, and BDNF plasma sampling. The results of this study demonstrate that individuals with AS suffer from significant developmental delay, impaired adaptive behavior, and sleep disruption. Additionally, hyperactivity/impulsivity appears to be the primary behavioral domain noted in these individuals. The majority of individuals in this project met criteria for autism spectrum disorder on the Autism Diagnostic Observation Schedule (ADOS); however, a negative correlation was noted between ADOS score and developmental age. BDNF plasma levels in AS individuals were significantly elevated compared to neurotypical controls. This is the first report of abnormal BDNF levels in AS, and one that necessitates larger future studies. The results provide a clue to understanding abnormal neuronal development in AS and may help guide future AS research. © 2015 Wiley Periodicals, Inc.